It depends on what variable you are tying to solve for first. Say you are trying to solve for x first and then y on the first problem you wrote.
In substitution you solve one of the equations for example with
6x+2y=-10
2x+2y=-10
you solve 2x+2y=-10 for x
2x+2y=-10
-2y = -2y (what you do to one side of the = you do to the other)
2x=-10-2y (to get the variable by its self you divide the # and the variable)
/2=/2 (-10/2=-5 and -2y/2= -y or -1y, they are the same either way)
x=-5-y
now you put that in your original equation that you didn't solve for:
6(-5-y)+2y=-10 solve for that
-30-6y+2y=-10 combine like terms
-30-4y=-10 get the y alone and to do this you first get the -30 away from it
+30=+30
-4y=20 divide the -4 from each side
/-4=/-4 (20/-4=-5)
y=-5
now the equation you previously solved for x can be solved for y.
x=-5-y
x=-5-(-5) a minus parenthesis negative -(- gives you a positive
-5+5=0
x=0
and now we have solved the problem. x=0 and y=-5
Answer:
hi
Step-by-step explanation:
Your final Andrew will be letter c
The new coordinates are (3, 1)
Answer:
Let's simplify step-by-step.
3x2+9x+6−(8x2+3x−10)+(2x+4)(3x−7)
Distribute:
=3x2+9x+6+−8x2+−3x+10+(2x)(3x)+(2x)(−7)+(4)(3x)+(4)(−7)
=3x2+9x+6+−8x2+−3x+10+6x2+−14x+12x+−28
Combine Like Terms:
=3x2+9x+6+−8x2+−3x+10+6x2+−14x+12x+−28
=(3x2+−8x2+6x2)+(9x+−3x+−14x+12x)+(6+10+−28)
=x2+4x+−12
Answer:
=x2+4x−12